Malignant transformation of calcifying cystic odontogenic tumour – a review of literature - Tarakji, Bassel; Ashok, Nipun; Alzoghaibi, Ibrahim; Altamimi, Mohammed Alsakran; Azzeghaiby, Saleh Nasser; Baroudi, Kusai; Nassani, Mohammad Zakaria (Contemporary Oncology/Współczesna Onkologia, 2015)
Calcifying cystic odontogenic tumour (CCOT) has been classified as an odontogenic tumour. Ghost cell odontogenic carcinoma (GCOC) is the malignant counterpart of CCOT. This paper aims to review the literature regarding malignant transformation of CCOT. A literature search was done via the National Library of Medicine PubMed interface, searching for articles relating to malignant transformation of CCOT. From these articles, references were obtained, and from their references lists, pertinent secondary references were also identified and acquired. After reviewing the literature, we found 26 cases of GCOC which developed from CCOT. Malignant transformation of CCOT was seen more commonly in the maxilla. Histologically, changes such as increased nuclear/cytoplasmic ratio, atypical mitotic figures have been reported after malignant transformation. Immunohistochemical analysis has shown an increased expression of ki-67 and p53 in tumour cells. Malignant transformation of CCOT, although rare, mostly takes place in recurrent and long standing cases.